Synthesis of Axially Chiral Bibenzo[g]coumarin Derivatives by Rhodium-Catalyzed Oxidative Annulation of Thiocarbamates - Takishima, Ryo; Ghosh, Koushik; Nishii, Yuji; Miura, Masahiro (Synlett, 2023)
Polyaromatic organic compounds have attracted significant attention because of their wide range of applications in various functional materials. Recently, transition-metal-catalyzed C–H bond activation and the subsequent oxidative cyclization with unsaturated compounds has emerged as a promising synthetic method for multiring systems. We report a two-step synthesis of binaphthyl-fused chiral bibenzo[g]coumarin derivatives by Rh-catalyzed annulative coupling reaction of BINOL-based thiocarbamates with alkynes. The optical properties of the coupling products were evaluated.
Keywords: coumarins; rhodium catalysis; C–H bond activation; BINOLs; circular dichroism; polycyclic heteroaromatic compounds